2017
DOI: 10.1590/1678-77572016-0046
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA extraction from whole saliva that was fresh or stored for 3, 6 or 12 months using five different protocols

Abstract: Saliva when compared to blood collection has the following advantages: it requires no specialized personnel for collection, allows for remote collection by the patient, is painless, well accepted by participants, has decreased risks of disease transmission, does not clot, can be frozen before DNA extraction and possibly has a longer storage time. Objective andMaterial and Methods This study aimed to compare the quantity and quality of human DNA extracted from saliva that was fresh or frozen for three, six and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 17 publications
4
22
0
3
Order By: Relevance
“…Furthermore, it is known that urinary and salivary DNA contain coextracted microbial nucleotides present in these biofluids, which could lead to an overestimation of the actual human DNA concentration measured by both of these nonspecific spectrophotometric or fluorometric methods. 23,26,40,49 The use of a real-time qPCR assay using the human-specific b-globin primers, overcomes these overestimations by determining more specifically the amount of human-intact amplifiable DNA in the total DNA extracted from urine or saliva. Our results showed that the DNA extracted from saliva contains a significant proportion of human intact DNA fragments of at least 164 bp long in contrast with the urinary DNA for which this human proportion could not be determined because it was below the detection limit for most of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is known that urinary and salivary DNA contain coextracted microbial nucleotides present in these biofluids, which could lead to an overestimation of the actual human DNA concentration measured by both of these nonspecific spectrophotometric or fluorometric methods. 23,26,40,49 The use of a real-time qPCR assay using the human-specific b-globin primers, overcomes these overestimations by determining more specifically the amount of human-intact amplifiable DNA in the total DNA extracted from urine or saliva. Our results showed that the DNA extracted from saliva contains a significant proportion of human intact DNA fragments of at least 164 bp long in contrast with the urinary DNA for which this human proportion could not be determined because it was below the detection limit for most of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva also represents an attractive biofluid source option for the detection of SARS-CoV-2, due to being non-invasive, easy-to-access, and low-cost, as well as having the ability to "mirror" systemic and local disease status [50]. It is well-known that saliva harbors a wide range of circulatory components (Figure 2), such as pro-inflammatory cytokines [51,52], chemokines [53], matrix metalloproteinases [54,55], mitochondrial DNA [56], genomic DNA [57], bacteria [58], SARS-CoV and SARS-CoV-2 virus [30,31,59], SARS-CoV antibodies [59], miRNAs [60], and extracellular vesicles (EVs) [61]. Furthermore, saliva samples can be stored at -80 • C for several years with little degradation [62].…”
Section: The Versatility Of Saliva For Covid-19 Diagnosismentioning
confidence: 99%
“…The kit’s procedure was modified by the collection and isolation of saliva DNA from 1 ml of preserved saliva samples, and overnight sample incubation with proteinase K. Isolated DNA was suspended in ddH20. NorgenBiotek commercial kits, the manufacturer’s instructions were followed [17].…”
Section: Methodsmentioning
confidence: 99%
“…The 260/280 nm absorbance ratio between 1.6 and 2.0 for samples were considered pure. Ratio lower than 1.6 testifies to higher protein contaminates [17,18].…”
Section: Methodsmentioning
confidence: 99%